Synthesis and Characterization of Complexes of 2-Hydroxy-3-nitro acetophenyl thiosemicarbazone with Some 3d Series Transition Metals - Shakti, Shiva; Mishra, P.M.; Mishra, Satyendra Kumar; Jha, Ajay Kumar (Asian Journal of Chemistry, 2010)
The preparation, properties, elemental analysis, magnetic susceptibility, electrical conductivity, electronic and IR spectral properties of the ligand 2-hydroxy-3-nitro acetophenyl thiosemicarbazone and its complexes with chromium(III), iron(III), copper(II) and manganese(II) have been discussed. On the basis of these observations, probable structures of all the metal complexes have been assigned.